2017
DOI: 10.1002/ana.24820
|View full text |Cite
|
Sign up to set email alerts
|

Robust graft survival and normalized dopaminergic innervation do not obligate recovery in a Parkinson disease patient

Abstract: Objective The main goal of dopamine cell replacement therapy in Parkinson disease (PD) is to provide clinical benefit mediated by graft survival with nigrostriatal reinnervation. We report a dichotomy between graft structure and clinical function in a patient dying 16 years following fetal nigral grafting. Methods A 55-year-old levodopa-responsive woman with PD received bilateral putaminal fetal mesencephalic grafts as part of an NIH-sponsored double-blind sham-controlled trial. The patient never experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 37 publications
0
70
0
Order By: Relevance
“…Although simply providing dopamine to the striatum may have provided benefit in some cases, it may not always be sufficient. An illuminating analysis of the brain of a PD patient who had received a fetal mesencephalic implant showed that despite a substantial population of surviving neurons, and a virtually complete restoration of striatal dopaminergic innervation, there was no clinical benefit . One possible explanation for these observations is that ectopic placement of dopamine neurons in the striatum, even in the presence of abundant neurite outgrowth, does not restore system or circuit properties of endogenous SN dopamine neurons.…”
Section: New Axon Growth: Advantages and Disadvantagesmentioning
confidence: 99%
“…Although simply providing dopamine to the striatum may have provided benefit in some cases, it may not always be sufficient. An illuminating analysis of the brain of a PD patient who had received a fetal mesencephalic implant showed that despite a substantial population of surviving neurons, and a virtually complete restoration of striatal dopaminergic innervation, there was no clinical benefit . One possible explanation for these observations is that ectopic placement of dopamine neurons in the striatum, even in the presence of abundant neurite outgrowth, does not restore system or circuit properties of endogenous SN dopamine neurons.…”
Section: New Axon Growth: Advantages and Disadvantagesmentioning
confidence: 99%
“…Late‐onset individuals (age 70 and older) tend to have more severe motor deficits, a postural instability gait disorder, lower susceptibility to levodopa‐induced dyskinesias, and more rapid disease progression. Furthermore, evidence from both preclinical and clinical studies of cell transplantation indicate that despite implantation of immature DA neurons that are at a developmental stage optimal for neurite outgrowth and innervation, the environment of the aged brain inhibits functional reconstitution otherwise present in younger individuals . There are biological variables that could explain many of these features such as the difference in neuronal progenitor proliferation, integration, innervation, and function between young and aged individuals; however, this concept would need further empirical verification.…”
mentioning
confidence: 99%
“…These findings raise serious questions about the interpretation of striatal DAT SPECT and other presynaptic molecular imaging markers of nigrostriatal neurons and may explain the discord between such molecular imaging and clinical measures of progression in multiple clinical studies . Furthermore, longitudinal, long‐term studies of PD using molecular imaging biomarkers of presynaptic nigrostriatal neurons have greater risk of running into this discrepancy.…”
mentioning
confidence: 99%